Technology elements of growing of savory and giant hyssop in the Lower Volga Region - Y.K. Zemskova; E.B. Lyalina; N.B. Suminova (Овощи России)
The production of environmentally safe agricultural products, such as foods and raw material for perfumery, cosmetology, and pharmacological industry is very important today. For the first time the morphological and technological features of spicy-flavor savory and giant hyssop were studied in the condition of Lower Volga Region. The efficiency of the cultivation of these crops in chernozemic zone has been shown.